PENGARUH KOMPENSASI DAN USIA TERHADAP LOYALITAS KARYAWAN - Wulandari, Ayu (Fakultas Ekonomi Universitas IBA, 2018)
This study aims to examine the effect of variable compenation and age on employee loyalty PT Asuransi Tri Pakarta Palembang either simultaneously or partially. Using employee sample of 25 people, the data were collected either through questionnaires or documents and then analyzed using descriptive statistics and parametric statistics (multiple linear regression), it was concluded that the computation and employee age variables simultaneously had significant and positive influence employee loyalty variable PT Asuransi Tri Pakarta Palembang. And only partially variable compensation alone capable of significantly affect employee loyalty variable, while the age of employees have no significant effect.